Green Synthesis Nanopartikel Tembaga (CuNP) Menggunakan Ekstrak Buah Naga Merah (Hylocereus polyrhizus) sebagai Aplikasi Lapisan Tipis - Karim, Afdal; Mardiansyah, Dedi; Dahlan, Dahyunir (Universitas Andalas, 2025)
Copper nanoparticle (CuNP)-based thin films have great potential in various technological applications, such as electronics, catalysts, and sensors, due to their high conductivity value and enhanced surface reactivity. This study aims to fabricate CuNP-based thin films using the spraying method, which is known to be efficient for material deposition on substrates. In the spraying process, copper nanoparticles are sprayed on a transparent glass substrate and dried at room temperature to form a homogeneous thin layer. Characterization of the thin films using UV-Vis spectrophotometer to determine the energy band gap and transmittance value. The results of testing the energy band gap of copper nanoparticles with a ratio of 1, 2, 3, 4, and 5 amounted to 3.03 eV, 3.09 eV, 3.11 eV, 3.17 eV and 3.25 eV. Meanwhile, the transmittance test results show that the percentage of thin layer transmittance ranges from 20% to 90% with good crystal quality and a smaller energy band gap that has high electrical conductivity so that the thin layer produced has a decent quality to be applied to printed electronic devices.